Molecular mass distribution and structural characterization of liquefaction products of a biomass waste material - Karaca, F (AMER CHEMICAL SOC, 2006)
A sample of pine barks has been liquefied in a tetralin-creosote oil mixture, under 30 bar hydrogen at 350 degrees C. The overall conversion was 96.3% (by wt). The product slurry was fractionated to hexane, toluene, and tetrahydrofuran solubles. Gas plus hexane solubles accounted for 32.4% of the product, while toluene solubles and tetrahydrofuran solubles were 6.7 and 57.2%, respectively. The fractions were examined by size exclusion chromatography, UV-fluorescence, and FT-infrared spectroscopy. In size exclusion chromatography, the toluene-and tetrahydrofuran-soluble fractions gave large peaks for material excluded from column porosity, suggesting the presence of high molecular mass material. The concentration of large molecular mass material increased from hexane solubles to toluene solubles and tetrahydrofuran solubles. UV-fluorescence spectra of the fractions showed shifts to shorter wavelengths and gains in intensity with increasing elution times in SEC. The structures and molecular masses of the product mixture do not appear amenable to upgrading by conventional catalytic methods.
Keywords: SIZE-EXCLUSION CHROMATOGRAPHY; COAL-DERIVED MATERIALS; TAR PITCH; PLANAR CHROMATOGRAPHY; BED REACTOR; PYROLYSIS; LIQUIDS; SPECTROMETRY; 1-METHYL-2-PYRROLIDINONE; FRACTIONATION; Energy & Fuels; Engineering